PENERAPAN METODE DEMONSTRASI DALAM MENGOPTIMALKAN HASIL BELAJAR PADA MATERI FIQIH DI MTS IBADURRAHMAN MALANG - Frenda Arif Ernando Putra; Zainul Arifin (Journal Islamic Studies, 2024)
The existence of methods in learning is very important. There are many methods that can be applied to fiqh learning, one of which is the demonstration method. The application of demonstration methods in fiqh learning is to help teachers deliver material and provide understanding to their students. This research uses a qualitative research approach field study This research aims to describe the application of demonstration methods in optimizing student learning outcomes in fiqih learning in MTs Ibadurrahman Sukun Malang as well as the advantages and disadvantages of applying demonstration methods to fiqih learning in MTs Ibadurrahman Sukun Malang